2018
DOI: 10.1016/j.anr.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Quantitative Electroencephalography Based Neurofeedback Training on Autonomous Regulations in Patients with Alcohol Use Disorder

Abstract: Neurofeedback training is recommended for improving autonomous regulation in alcohol use disorder as a nursing intervention. However, for significantly attenuating hyperarousal through brain wave correction, it may be necessary to increase the number of neurofeedback sessions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…In relation to the study design, four studies were randomised clinical trials with two groups, experimental and control; one was a case study [43]; and three studies were non-randomised clinical trials [38][39][40]. Among the clinical trial studies, two included an experimental and a control group, in which the latter was maintained on treatment as usual (TAU) procedures [41,42]; one study with an AUD experimental group, an AUD control group kept in TAU and a no-AUD control who underwent neurofeedback sessions [15]; and another one included a non-equivalent pretest-posttest control group, in which participants were randomised in disproportionate groups of individuals, divided in experimental and control on TAU [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the study design, four studies were randomised clinical trials with two groups, experimental and control; one was a case study [43]; and three studies were non-randomised clinical trials [38][39][40]. Among the clinical trial studies, two included an experimental and a control group, in which the latter was maintained on treatment as usual (TAU) procedures [41,42]; one study with an AUD experimental group, an AUD control group kept in TAU and a no-AUD control who underwent neurofeedback sessions [15]; and another one included a non-equivalent pretest-posttest control group, in which participants were randomised in disproportionate groups of individuals, divided in experimental and control on TAU [20].…”
Section: Resultsmentioning
confidence: 99%
“…However, Ko and Park [20] investigated the reduction of brain hyperexcitation by inhibiting high‐frequency beta waves, which are usually excessive in people who abuse alcohol, and increasing the alpha frequency, using the alpha‐beta protocol. They found promising results, opening the question about the specificity of the alpha‐theta protocol or, also, if the main effect of neurofeedback in this population is the modulation of alpha, regardless of whether the reinforcement is given for the alpha/beta or alpha/theta ratio.…”
Section: Discussionmentioning
confidence: 99%
“…The gamma/γ powers, but not other frequency bands, were elevated across the cortex of patients with AUD (Bauer, 2001). However, Ko and Park showed that there was a reduction in alpha/α power while an increase in gamma/γ powers (Ko & Park, 2018). Interestingly, by analyzing EEG obtained from 191 male alcoholic patients, Coutin-Churchman et al revealed that the most frequent reduction took place in the delta/δ and theta/θ bands (Coutin-Churchman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As the brain's executive center is responsible for advanced thinking skills, the prefrontal cortex forms personality, regulates the depth of emotions (such as anger and aggression) and controls logical thinking. QEEG has a long history and its clinical usefulness has gradually become well-known [17][18][19][20]. The rapid development of desktop computers in the 1990s placed QEEG technology in the hands of clinicians.…”
Section: Introductionmentioning
confidence: 99%